A comparative evaluation of porous hydroxyapatite bone graft with and without platelet-rich plasma in the treatment of periodontal intrabony osseous defects: A clinico-Radiographic study - Gouri Bhatia; Manish Khatri; Mansi Bansal; Sameer Saxena; Vipin Agarwal; Ashish Kumar (Wolters Kluwer Medknow Publications, 2018)
Background: Today, regenerative attempts for treatment of periodontal disease focus on the introduction of a filler material into the defect in hope of inducing bone regeneration. The purpose of this study was to clinically and radiographically evaluate the use of porous hydroxyapatite bone graft with and without platelet-rich plasma (PRP) in the treatment of intrabony defects. Materials and Methods: The study was carried out in ten patients between 18 and 60 years. Patients with pocket depth ≥5 mm and radiographic evidence of vertical bone loss in the affected site were randomly assigned to treatment with a combination of PRP + Hydroxyapatite (HA) (test sites) or HA alone (control sites). The parameters were compared at baseline and 6 months postoperatively. Results: There was a statistically significant reduction in probing depth and gain in clinical attachment in both the groups individually (more in experimental group); however, on comparing the two groups, the net reduction was not significant. Radiographic assessment showed a decrease in the defect size in both the groups. Conclusion: PRP in addition to a bone graft in the treatment of intrabony defects is safe and shows improved defect fill as compared to the use of bone graft alone.